Antipassive typology, diachrony, and related constructions - Janic, Katarzyna; Witzlack-Makarevich, Alena (Typological studies in language, 2021)
"This book provides a comprehensive treatment of the morpho-syntactic and semantic aspects of the antipassive construction from synchronic, diachronic, and typological perspectives. The nineteen contributions assembled in this volume address a wide range of aspects pertinent to the antipassive construction, such as lexical semantics, the properties of the antipassive markers, as well as the issue of fuzzy boundaries between the antipassive construction and a range of other formally and functionally similar constructions in a genealogically and areally diverse languages. Purely synchronically oriented case studies are supplemented by contributions that shed light on the diachronic development of the antipassive construction and the antipassive markers. The book should be of central interest to many scholars, in particular to those working in the field of language typology, semantics, syntax, and historical linguists, as well as to specialists of the language families discussed in the individual contributions"--